Task-shifted approaches to postdiagnostic dementia support: a qualitative study exploring professional views and experiences - Louise Robinson; Greta Rait; Claire Bamford; Jill Manthorpe; Rachael Frost; Jane Wilcock; Karen Harrison Dening; Martin Knapp; Sube Banerjee; Joy Adamson; Alistair Burns; Raphael Wittenberg; et al. (BMJ Open)
Objectives To explore the views of commissioners, service development leads, service managers and senior staff in selected dementia services on increasing the role of primary care in postdiagnostic support for people with dementia.Design Qualitative semi-structured telephone interviews and a focus group.Setting Participants were drawn from National Health Service (NHS) Clinical Commissioning Groups, social care commissioning and a range of dementia services across primary care, secondary mental healthcare, social care and the third sector. All participants were based in England or Wales.Participants 61 professionals, comprising 25 commissioners or service development leads; 25 service managers; and 11 team leads or senior staff.Results Participants had varied views on whether a primary care-based approach for postdiagnostic support for people with dementia and their families was appropriate, achievable and/or desirable. Potential benefits of a task-shifted approach were continuity and a more holistic approach to care; familiarity for both patients and staff; and reduction of stigma. Key challenges included the capacity, ability and inclination of primary care to deliver postdiagnostic support for people with dementia and their families. We discovered a number of conceptual challenges to implementing a task-shifted and task-shared approach, including uncertainties around the nature of postdiagnostic support, the definition of primary care and identification of tasks that could be shifted to primary care.Conclusions Our data highlight the concerns of key professional staff around greater involvement of primary care in postdiagnostic support for dementia. Further research is needed to achieve a shared understanding and consensus over what postdiagnostic support means in the context of dementia. We will be undertaking such research in the next phase of our programme.